Reported energy intake versus estimated energy requirements of Portuguese adolescents and young adults - Tallon, José Maria; Narciso, Janine; Saavedra, Raquel; Barros, Ana; Silva, António José; Costa, Aldo Matos (Progress in Nutrition, 2020)
Introduction/objective: Predictive equations are commonly used to estimate basal metabolic rate/resting metabolic rate and determine energy requirements, with the Harris-Benedict equation being amongst the most study equations. However, if this formula effectively addresses basal metabolic rate/resting metabolic rate in individuals living in contemporary societies is still unclear. In the present study we compared the energy intake of Portuguese adolescents/young adults with their energy requirements by gender, age and Body Mass Index category. Methods: This was a cross-sectional study that included 287 participants from the 9th to the 12th grade, that recorded their food intake for at least 3 days in an online platform and had complete anthropometric data. The Harris-Benedict equations were used to estimate the energy requirements of adolescents/young adults. Results: Overall energy intake of adolescents/young adults was significantly lower than their requirements (1898.6 kcal versus 2047.1 kcal, p<0.001; Cohen’s d= -0.42). The same was observed for both genders, with girls having a reported energy intake (REI) of 1847.9 kcal and estimated energy requirements (EER) of 1912.5 kcal (p=0.011; Cohen’s d= -0.18); and boys a REI of 2002.6 kcal and an EER of 2323.5 kcal (p<0.001; Cohen’s d= -1.09). Additionally, REI was significantly lower than EER for adolescents (1896.4 kcal versus 2052.9 kcal, p <0.001; Cohen’s d= -0.45), normal weight (1896.8 kcal versus 2014.3 kcal, p <0.001; Cohen’s d= -0.33), overweight (1912.5 kcal versus 2214.1 kcal, p<0.001; Cohen’s d= -1.03) and obese adolescents/young adults (1964.1 kcal versus 2362.2 kcal, p<0.001; Cohen’s d= -2.14). Conclusion: The energy intake of adolescents/young adults was significantly lower than their requirements for both genders, adolescents, normal weight, overweight and obese individuals (p<0.05).